A repercussão da lei nª14.454/2022 na cobertura obrigatória dos planos de assistência à saúde - (:unkn) unknown (Universidade Brasil, 2023)
The present work aims to understand the legislative movement for the resolution of the controversy of the legal nature of the "List of Procedures of the ANS" through the enactment of Law number 14.454/2022, through the analysis of the right to health as a constitutional guarantee, the formation of contracts of health care plans and jurisprudential precedents on the subject. This is because there was a great legal divergence between the courts to analyze the need to cover treatments and/or procedures that were not foreseen in the aforementioned list. For this purpose, exploratory research of a qualitative nature is used, embodied in bibliographical and documentary research, as well as analysis of the abundant jurisprudence that has developed over the years on the subject. From this, the repercussion that the new law will have for society and for the agreements is problematized, under the financial and constitutional focus, as well as the overlap of the public interest over the private one. It is concluded that the constitutional right to health will remain guaranteed, but the judicialization of the issue continues under different aspects and in the face of different subjects, until a new law or decision comes in that is capable of efetível remedying the issue
Keywords: Lei nº 14.454/2022; Rol de procedimentos da ANS; Interesse público; Plano de saúde; CH